059 Maternal and paternal smoking during pregnancy and trajectories of growth and adiposity in the offspring. (16th November 2010) - Howe, L D; Matijasevich, A; Tilling, K; Lawlor, D A
Abstract : Objective: To explore the associations of maternal smoking during pregnancy with offspring trajectories of height, weight and adiposity and to compare these with associations with paternal smoking to determine whether any associations are driven by intrauterine mechanisms. Design: Individual trajectories of height, weight and adiposity were modelled from birth to 10 years using random-effects linear-spline models. Adiposity was modelled as ponderal index (PI, kg/m 3 ) from birth to 2 years and body mass index (kg/m 2 ) from 2 to 10 years. Interactions between self-reported maternal and paternal smoking during pregnancy (any vs none) with trajectories of height, weight, and adiposity were examined with and without adjustment for potential confounders and mutual adjustment for maternal/paternal smoking. Setting: South-West England. Participants: N=12 684 children for height models, 12 773 for weight models, 12 531 for PI models, and 11 588 for body mass index models. Results: Maternal smoking during pregnancy had a strong impact on birth length and weight (eg, reduction in birth length in boys 0.70 cm, SE 0.07). These effects reduced only slightly with adjustment for confounders and paternal smoking during pregnancy. Paternal smoking was associated with much smaller reductions in birth length and weight (eg, reduction of birth length in boys 0.21 cm, SE 0.07), and associations were completely attenuated by adjustment for confounders and maternal smoking in pregnancy. There was some evidence that parental smoking during pregnancy affected height growth in later infancy (3–10 months) and weight gain in early and later infancy (0–4 and 4–11 months), with offspring of parents who smoked growing and gaining weight faster than offspring of non-smokers. Associations were stronger for maternal than paternal smoking. Height growth and weight gain in later childhood was not associated with smoking in pregnancy. The offspring of parents who smoked had lower PI at birth (eg, reduction in PI at birth for maternal smoking in pregnancy among boys −0.25 kg/m3, SE 0.08), with maternal smoking having a stronger association than paternal smoking. However, associations of both maternal and paternal smoking during pregnancy on PI at birth were completely removed by adjustment for confounders. Neither maternal nor paternal smoking was associated with adiposity trajectories. Conclusion: There is evidence of an intrauterine effect of maternal smoking on birthweight and length and on height and weight growth in infancy (but not later childhood). Maternal smoking in pregnancy does not seem to affect adiposity at birth or change in this during infancy or childhood through intrauterine mechanisms.